2021
DOI: 10.3390/su13031032
|View full text |Cite
|
Sign up to set email alerts
|

An Online-Based Edu-Escape Room: A Comparison Study of a Multidimensional Domain of PSTs with Flipped Sustainability-STEM Contents

Abstract: The use of active and flipped methodologies has increased in recent years. Here, gamification uses typical elements of a game in different contexts, including that of education. Specifically, Escape Room games used as educational tools have potential for teaching–learning, and they can be beneficial because they can improve students’ motivation and emotions toward learning. This is particularly valuable in science, technology, engineering and mathematics (STEM) courses, where the cognitive factor and multidime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
0
26
0
2
Order By: Relevance
“…It is stated in the literature that the implementation of innovative, motivating, and collaborative activities in secondary education science classes increases motivation, interest, and positive emotions (Ritchie et al, 2011;Tomas and Ritchie, 2012). Our research group has demonstrated, for instance, how the implementation of active, motivating, and innovative methodologies improves attitude and emotions toward scientific disciplines and definitely it is demonstrated that emotions are implied in what the student learns (Sánchez-Martín et al, 2020;Hernández-Barco et al, 2021;Yllana et al, 2021). Future research will be to design an intervention program based on the development of practical classroom activities associated with specific content.…”
Section: Discussionmentioning
confidence: 60%
“…It is stated in the literature that the implementation of innovative, motivating, and collaborative activities in secondary education science classes increases motivation, interest, and positive emotions (Ritchie et al, 2011;Tomas and Ritchie, 2012). Our research group has demonstrated, for instance, how the implementation of active, motivating, and innovative methodologies improves attitude and emotions toward scientific disciplines and definitely it is demonstrated that emotions are implied in what the student learns (Sánchez-Martín et al, 2020;Hernández-Barco et al, 2021;Yllana et al, 2021). Future research will be to design an intervention program based on the development of practical classroom activities associated with specific content.…”
Section: Discussionmentioning
confidence: 60%
“…Finally, the loads of each item were close to or greater than the recommended value (>0.700). Considering such values, the reliability and validity of the constructs could be granted [46]. ried out to get a better understanding of the instruction designed on the components involved in this research: the PSTs own beliefs and conceptions, positive and negative attitudes toward mathematics learning, and the influence of their educational background.…”
Section: Resultsmentioning
confidence: 99%
“…When designing an educational Escape Room, it is essential to consider a well-defined educational boundary conditions and to create hybrid learning spaces that can foster the learners' transfer from the school context to the game context (Veldkamp et al, 2020). Furthermore, there has been an increase in the number of studies on educative Escape Room and Breakout in recent years, which shows the increasing curiosity concerning these didactic tools in the education research environment (Taraldsen et al, 2020;Yllana-Prieto et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%